Stability analysis and control of embankment with solid backfill coal mining. (3rd April 2017) - Sun, Qiang; Zhou, Nan; Quan, Kai; Chen, Yong
Abstract: This paper introduces a longwall mining attempt at Jining No. 3 Coal Mine. A solid backfill coal mining method was first applied to exploit the coal resources buried under the Nanyang Lake embankment. A numerical model was established based on analysis of geological conditions in the area and the structural characteristics of the embankment. This model was used to study the two key factors that influence the embankment deformation: the backfill body's compression ratio and the working face advancing distance. The measured results from Nanyang Lake embankment show that the maximum value of the surface subsidence was only 68 mm, and the maximum values of the horizontal strain and incline strain were 0.16 and 0.18 mm/m, respectively. The measured backfill body's compression ratio was approximately 89.1%. Field demonstrations have shown that solid backfill mining is effective in controlling strata movement and surface deformation.